PROFESSIONAL STANDARDS IN INTERPRETING SPHERE AND EDUCATIONAL REQUIREMENTS TO ITS TRAINING - Сімкова, Ірина Олегівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article deals with requirements to translation/interpreting training, they are considered on the ground of foreign (American, British, and Australian) professional standards comparison. The list of qualities that are necessary for the future translators in their professional activity, depending on the complexity of the document is given. The educational requirements to the professional activity of interpreter/translator; conditions of sight translation performance; knowledge, skills, and sub-skills necessary for sight translation performance (knowledge of the translation process, knowledge of the target language and the source language at the appropriate level) are analysed. The potential problems that could make difficult the implementation and evaluation of the sight translation are described. The recommendation on practical implementation of sight translation course is proposed